Minimally invasive approach to the treatment of enamel white spot lesions with infiltrating resins. A report of two cases - Toscano , Marina Andrea (2025)
Enamel white spot lesions can result from early carious lesions, fluorosis, molar hypomineralization (MH), or trauma-induced hypomineralization. Histologically, these defects exhibit a reduction in the mineral phase and replacement by organic fluids. Such lesions can be managed using a minimally invasive approach with infiltrating resins. These low-viscosity resins can penetrate the lesion body by capillary action, restoring the enamel's natural translucency while simultaneously enhancing the mechanical strength of hypomineralized enamel. The technique involves superficial demineralization to allow access to the lesion through the application of 15% hydrochloric acid (HCl), followed by resin infiltration into the lesion body. Depending on the etiology, extent, and depth of the lesion, the erosion-infiltration protocol may not always be sufficient and might need to be complemented with other techniques to achieve deeper penetration and effectively infiltrate the lesion. This report presents two clinical cases treated with superficial and deep infiltration techniques, the latter combined with microabrasion, to address white spot lesions caused by caries and MH, respectively. Microinfiltration is presented as a conservative and effective method for treating enamel white spot lesions. A precise diagnosis is essential to select the most appropriate approach and ensure predictable outcomes.